Synthesis and Characterization of Gold(III) Complexes with bis-(1,4-Sodium thioglycolate)butane Ligand - A. Abdalrazaq, Eid; H. Buttrus, Nabeel; Al-Moujod M. Abd Al-Rahman, Abd (Asian Journal of Chemistry, 2010)
The new ligand bis(1,4-sodium thioglycolate)butane (L) –O2CCH2S(CH2)4SCH2CO2–, has been prepared from the reaction of disodium salt of mercaptoacetic acid and 1,4-dichlorobutane. Mono, di and tetranuclear complexes were obtained by direct reaction of the bis-(1,4-sodium thioglycolate)butane with H[AuCl4] in 1:1, 1:2, 2:2 and 4:2 metal:ligand molar ratio. The prepared complexes were characterized by elemental analysis, spectral studies FT-IR and UV-Vis, magnetic measurement, conductivity measurement and 1H NMR for the ligand. The electrical conductance data indicate that the complexes of the formula [Au(L)]Cl, Na[Au(L)2] and [Au3(L)2Cl4][AuCl4] are 1:1 electrolyte and [Au4(L)2Cl6]Cl2 is 1:2 electrolyte. Electronic spectra and magnetic moment values indicate the presence of square planner geometry around the Au(III) ion. Molecular modeling program MM2 is used to determine the most stable isomer which coincidence with experimental results.